Particulate Shiga Toxin 2 in Blood is Associated to the Development of Hemolytic Uremic Syndrome in Children - Brigotti, Maurizio; He, Xiaohua; Carnicelli, Domenica; Arfilli, Valentina; Porcellini, Elisa; Galassi, Elisabetta; Tazzari, Pier Luigi; Ricci, Francesca; Patfield, Stephanie A.; Testa, Sara; Paglialonga, Fabio; Picicco, Damiano; Caprioli, Alfredo; Scavia, Gaia; Morabito, Stefano; Ardissino, Gianluigi (Thrombosis and Haemostasis, 2020)
Hemolytic uremic syndrome (HUS), the leading cause of acute renal failure in children (< 3 years), is mainly related to Shiga toxins (Stx)-producing Escherichia coli (STEC) infections. STEC are confined to the gut resulting in hemorrhagic colitis, whereas Stx are delivered in blood to target kidney and brain, with unclear mechanisms, triggering HUS in 5 to 15% of infected children. Stx were found on circulating cells, free in sera (soluble Stx) or in blood cell-derived microvesicles (particulate Stx), whereby the relationship between these forms of circulating toxins is unclear. Here, we have examined 2,846 children with bloody diarrhea and found evidence of STEC infection in 5%. Twenty patients were enrolled to study the natural course of STEC infections before the onset of HUS. In patients, Stx were found to be associated to circulating cells and/or free and functionally active in sera. In most children, Stx were bound to neutrophils when high amounts of toxins were found in feces. Time-course analysis showed that Stx increased transiently in patients' sera while the decrease of toxin amount on leukocytes was observed. Notably, patients who recovered (85%) displayed different settings than those who developed HUS (15%). The distinctive feature of the latter group was the presence in blood of particulate Stx2 (Stx2 sedimented at g-forces corresponding to 1 μm microvesicles) the day before diagnosis of HUS, during the release phase of toxins from circulating cells. This observation strongly suggests the involvement of blood cell-derived particulate Stx2 in the transition from hemorrhagic colitis to HUS.
Keywords: hemolytic uremic syndrome; Shiga toxin-producing Escherichia coli; bloody diarrhea; bacterial toxins